First principles study of electronic properties and optoelectronic performance of type-II SiS/BSe heterostructure. (8th February 2023) - Ullah, S. S.; Din, H. U.; Alam, Q.; Idrees, M.; Amin, Bin; Khan, W.; Farooq, M.; Nguyen, Cuong Q.; Nguyen, Chuong V.
Abstract : We perform first-principles calculations to explore the electronic structure, optical properties and photocatalytic performance of the SiS/BSe heterostructure. Abstract : The construction of van der Waals heterostructures have been extensively studied for the design of new devices for potential applications in nanotechnology and renewable energy. In this work, we perform first-principles calculations to explore the electronic structure, optical properties and photocatalytic performance of the SiS/BSe heterostructure. The SiS/BSe heterostructure is energetically and thermally stable in the ground state. The generation of the SiS/BSe heterostructure gives rise to a reduction in the band gap compared to the constituent monolayers, suggesting that the optical absorption of such a heterostructure can be enlarged. Furthermore, the formation of the SiS/BSe heterostructure leads to generation of type-II band alignment, which makes the heterostructure a promising candidate for photogenerated charge separation and light detection purposes. The absorption spectrum demonstrates broadening and red-shift in the SiS/BSe heterostructure. Additionally, the SiS/BSe heterostructure possesses suitable band edges and straddles the standard redox potentials, thus making it a potential candidate for photocatalytic water dissociation under solar light irradiation. These findings pave the way for practical applications of the SiS/BSe heterostructure for optoelectronics and photocatalytic applications.